PEMBERDAYAAN MASYARAKAT DAN DESA DI KABUPATEN LEBAK PROVINSI BANTEN - Rusito Rusito (LPPM STIA Banten, 2018)
The condition of villages in Indonesia, Banten Province and Lebak Regency are mostly still included in the category of disadvantaged villages and very left behind. Since the implementation of Law no. 6/2014 efforts to reduce underdeveloped villages and villages are underdeveloped continuously by providing village authorities and budget transfers by the Government and Local Government. All this is done so that villages are able to independently escape from the backwardness of escorting various government and local government empowerment programs. The purpose of this paper is to gain an understanding of community empowerment and village which has been done with case study in Lebak Regency of Banten Province. The framework used is Stewart's (1998: 77) thought that empowerment is done by enabling, facilitating, consulting, collaborating, mentoring and supporting. The conclusion of this writing that the empowerment of society and village in the object of study has been done with various programs and activities but the implementation is not maximized. Inadequate implementation of community empowerment programs and activities because of constrained geographical factors that are difficult and extensive, old habits of village government that are less supportive to apply the principles of good governance, human resources of district and sub-district apparatus and inadequate supporting cos